Transgraniczne usługi ubezpieczeniowe jako kierunek rozwoju jednolitego rynku europejskiego - Przybytniowski, Jarosław W. (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: The uniform market of insurance services functions on principle of harmonization of regulations relating minimum requirements in range: the uniform insurance license (“single passport”), the supervision provided by the country of seat of insurance company, liberty of founding the companies in both insurance sectors, requirement of technical reserves in reference to the whole of active bodies of institution, the requirement of year-old and consolidated reports + as well as special supervision over insurance groups (the supervision “solo plus ”). The number of foreign insurers, who on principle of liberty of service services notified the intention of leadership the activity in Poland after accession to EU growed up almost three times. In 2007 the number of notification growed up to 425. Simultaneously, the insurance companies with seat in Poland in more and larger degree get involved in transborder activity. The most national insurers posses notification on foreign activity on principle of liberty of service services (17 companies lead the activity in 27 countries).